Impaired macrophages and failure of steroidogenesis and spermatogenesis in rat testes with cytokines deficiency induced by diacerein - de Oliveira, Salmo Azambuja; Cerri, Paulo Sérgio [UNESP]; Sasso-Cerri, Estela [UNESP] (Springer Nature, 2021)
The role of cytokines in testicular function under normal conditions has not been completely understood. Here, we evaluated testicular macrophages (TM), steroidogenesis by Leydig cells (LC) and seminiferous tubules integrity in cytokines-deficient rat testes induced by diacerein, an anti-inflammatory drug that inhibits interleukin-1 (IL-1) and tumor necrosis factor-alpha (TNF-α). Male rats received daily 100 mg/kg of diacerein (DIAG; n = 8) or saline (CG; n = 8) for 30 days. Serum testosterone (T) levels were measured and the seminiferous tubule (ST) area, epithelial area (EA), frequency of damaged ST and number of Sertoli cells (SC) were evaluated. TUNEL method and immunoreactions for detection of pro-IL-1β, TNF-α, steroidogenic acute regulatory protein (StAR), 17β-hydroxysteroid dehydrogenase (17β-HSD), androgen receptor (AR) and scavenger receptor for hemoglobin-haptoglobin complexes (CD163), a TM marker, were performed. Testicular AR, 17β-HSD and IL-1β levels were detected by Western blot. Data were submitted to Student t test (p ≤ 0.05). In DIAG, T and testicular AR, 17β-HSD and IL-1β levels decreased significantly (p < 0.05). The number of TUNEL-positive interstitial cells increased and LC showed weak StAR, 17β-HSD and AR immunoexpression in association with reduced IL-1β immunoexpression and number of CD163-positive TM in the interstitial tissue from diacerein-treated rats. Numerous damaged ST were found in DIAG, and reduction in the EA were associated with germ cells death. Moreover, the number of SC reduced and weak AR and TNF-α immunoexpression was observed in SC and germ cells, respectively. The cytokines deficiency induced by diacerein impairs TM, LC and spermatogenesis, and points to a role of IL-1β in steroidogenesis under normal conditions. In the ST, the weak AR and TNF-α immunoexpression in SC and germ cells, respectively, reinforces the idea that TNF-α plays a role in the SC androgenic control.
Keywords: Anti-inflammatory; IL-1; Leydig cell; Macrophage; Spermatogenesis; TNF-α